Ecologia do fitoplâncton em áreas de cultivo de Tilápia do Nilo, Oreochromis niloticus, em tanques-rede no açude Ministro João Alves, Parelhas, Rio Grande do Norte - Pessoa, Emilly Kataline Rodrigues (2010)
The dams are limnic ecosystems of great importance for its multiple uses, among them, water supply for the public and to culture of artisanal fish are most relevant. The aim of the present study is to evaluate the physical-chemical characteristics and the phytoplankton community in two chosen sites (Point 1 littoral zone of point source; Point 2 pelagic zone of non-point source) of the Minister João Alves dam, which is also known as Boqueirão de Parelhas/RN. This represents the spatial distribution of the phytoplankton species in order to understand any possible alterations of the water quality and the phytoplankton composition in relation to the water quality originating from the impact of the tilapia, Oreochromis niloticus, culture. The study period also encompasses temporal variations exhibited in two seasons of an annual cycle, one during the dry season (Oct, Nov and Dec of 2008 and Jan of 2009), and the other rainy season (Mar, Apr, May and June of 2008) to extend the observation. The physicalchemical parameters, such as pH, temperature, electrical conductivity, concentration of dissolved oxygen were measured in situ and the values of the inorganic nutrients (nitrate, ammonium and orto-phosfato) and chlorophyll in the laboratory. The quali-quantitative analyses of the phytoplankton had been carried through sedimentation technique and the enumeration of the random of 400 cells, colonies and filaments counted using Sedgwick-Rafter counting chamber. The results of pH varied widely from the acidic to alkaline range with the minimum of 5.8 (± 0.8) and the maximum of 9.2 (± 0.7-0.8), at point 1 and 2. The dissolved oxygen content was higher in the rainy period than that in the dry period. The maximum electrical conductivity was of 1409 μScm-1 in point 1 and 431 minim of μScm-1, in point 2. There was a considerable alteration in the levels of inorganic nutrients such as nitrate-nitrogen, ammoniacal nitrogen and orthophosphate during the two cycles of study period. Phytoplankton assemblages presented a picture of alternate dominance among species Cyanobacteria, Bacillariophyceae and Chlorophyceae. The trophic state index diagnosed to the category of mesotrophic, which is based on the values of chlorophyll, total phosphorus and Secchi-disc measurements. The wind driven turbulence of the water column and the fresh inflow of water (flushing and dilution) during rainy season acted as constraint and did-not allow an exaggerated growth of the species of cyanobacteria. On the basis of the present we conclude that the culture of tilapias in cage-culture fails to produce pollution load that could compromise the quality of the water of the dam, probably be due to small dimension of the culture in relation to the size, volume of the water and the reservoir capacity support its own environment